Two philometrids (Nematoda: Philometridae) infecting the tigertooth croaker Otolithes ruber (Bloch & Schneider) (Teleostei: Sciaenidae) off Iran, including erection of a new genus - Moravec, František; Khosheghbal, Maryam; Pazooki, Jamileh (Systematic parasitology, 2013)
Two philometrid nematodes (Philometridae) are described from the marine perciform fish (tigertooth croaker) Otolithes ruber (Bloch & Schneider) (Sciaenidae) from off Iran: Clavinemoides annulatus n. g., n. sp. based on female specimens from the caudal fin of fish from the Persian Gulf and Philometra otolithi Moravec & Manoharan, 2013 from subgravid and nongravid females collected from the ovary of fishes in the Sea of Oman and the Persian Gulf. The monotypic genus Clavinemoides n. g. is mainly characterised by a triangular oral aperture, a markedly large anterior oesophageal bulb, a distinctly annulated body and numerous fine elevated transverse cuticular bands. The finding of P. otolithi in Iranian waters represents a new geographical record of this parasite species. An updated key to the genera of the Philometrinae Baylis & Daubney, 1926 is provided.
Keywords: Animals; Írán; Fish Diseases; zvířata; Male; ženské pohlaví; mužské pohlaví; Perciformes; Female; Iran; Indický oceán; Indian Ocean; Dracunculoidea; nemoci ryb